Evaluation of cohesion and friction angle of Kuantan clayey soil stabilised by recycled and reused materials mixed with lime - Solomon, Eugene Phang (2013)
This thesis deals with assessment for the cohesion and friction angle of Kuantan soils using variable reused and recycled materials. The objective of this thesis is to evaluate the value of cohesion and friction angle of Kuantan soils and also to determine the optimum percentage content of materials and stabiliser for soil improvement. Soil classification is to be done under USCS soil classification methods. Atterberg limits are tested by Casagrande's method. The thesis describes the triaxial tests done to assess the cohesion and friction angle, and identify the critical amount of stabiliser used. Powdered lime, crushed glass, shredded carpet fibres, fly ash, and shredded high density polyethylene plastic materials were used in this research. The values of cohesion and friction angle of Kuantan soils were done using a semi automatic triaxial machine under unconsolidated undrained conditions. Finally, the cohesion and friction angle of the samples obtained are employed as input to find the shear strength of Kuantan soil. From the results, it is observed that the analysis of using fly ash and crushed glass yields more conservative increment in cohesion and friction angle. The acquired results utilizing high density polyethylene and carpet fibres indicate that when the stabiliser is used at a higher percentage, it gives lower cohesion and friction angle than that the results obtained using crushed glass and fly ash. The obtained results indicate that the fly ash blend produces the highest shear strength.